Implementation of Accounting for Zakat and Infaq Funds at Baznas in Medan Based on PSAK No. 109 - Suhaila Zahra Lesmana; Laylan Syafina; Hendra Harmain (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This article is intended to analyze the application of accounting for Zakat and Infaq funds based on PSAK No. 109 at BAZNAS Medan in 2022. This research method used descriptive qualitative, also including field studies. Data were collected through observation, interviews, and documentation. Based on the analysis and discussion above, it can be concluded that BAZNAS Medan does not fully implement PSAK No. 109 in preparing and presenting its financial statements. The application of accounting for Zakat and Infaq funds is still not appropriate regarding the presentation and disclosure of financial statements. This study aims to analyze how the accounting for zakat and infaq funds is applied to BAZNAS in Medan based on PSAK 109. Report components based on PSAK No. 109 were also not realized properly, because it only presented two reports, namely reports on changes in funds and financial position, as for cash flow reports, notes on financial statements were not attached, while reports on non-halal funds themselves were included in infaq /alms funds. Apart from that, it also does not detail zakat fund transactions and only details it internally for Central BAZNAS. Thus, BAZNAS Medan is still lacking in applying Zakat and Infaq accounting based on PSAK No. 109. Researchers with this research hope to be able to contribute especially to the BAZNAS Medan in continuing to evaluate and improve the quality of its financial reports.